2013
DOI: 10.1038/cddis.2013.258
|View full text |Cite
|
Sign up to set email alerts
|

SAHA overcomes FLIP-mediated inhibition of SMAC mimetic-induced apoptosis in mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is a highly pro-inflammatory malignancy that is rapidly fatal and increasing in incidence. Cytokine signaling within the pro-inflammatory tumor microenvironment makes a critical contribution to the development of MPM and its resistance to conventional chemotherapy approaches. SMAC mimetic compounds (SMCs) are a promising class of anticancer drug that are dependent on tumor necrosis factor alpha (TNFα) signaling for their activity. As circulating TNFα expression is significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Not surprisingly, there is a wealth of data showing that FLIP is key determinant of resistance to TRAIL receptor agonists; however, it remains to be seen whether high FLIP expression will be a key clinical mechanism of resistance to the next generation of multi-valent TRAIL receptor agonists. We have also reported that FLIP is an important determinant of resistance to IAP antagonists, with FLIP preventing cell death induced in response to both monovalent and bivalent IAP antagonists by blocking caspase-8 activation at the ripoptosome [146,147]. More recently, we reported that acute induction of FLIP expression in response to MEK inhibition in BRAF mutant colorectal cancer results in resistance to MEK inhibitor-induced cell death [148].…”
Section: Flip As a Mediator Of Therapy Resistancementioning
confidence: 88%
“…Not surprisingly, there is a wealth of data showing that FLIP is key determinant of resistance to TRAIL receptor agonists; however, it remains to be seen whether high FLIP expression will be a key clinical mechanism of resistance to the next generation of multi-valent TRAIL receptor agonists. We have also reported that FLIP is an important determinant of resistance to IAP antagonists, with FLIP preventing cell death induced in response to both monovalent and bivalent IAP antagonists by blocking caspase-8 activation at the ripoptosome [146,147]. More recently, we reported that acute induction of FLIP expression in response to MEK inhibition in BRAF mutant colorectal cancer results in resistance to MEK inhibitor-induced cell death [148].…”
Section: Flip As a Mediator Of Therapy Resistancementioning
confidence: 88%
“…FLIP is a major apoptosis-regulatory protein frequently overexpressed in solid and hematological cancers and is an important mediator of chemo-and radio-resistance as well as apoptosis induced by immune effector cells and therapeutic agonists [35][36][37][38] . For these reasons, high FLIP expression has been correlated with poor prognosis in a number of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…MPM show aberrant CpG island methylation compared to normal pleura [39,40], even with an age [41]-and ethnicity [42,43] e dependent manner and it is the promoter of several known tumorsupressor genes that is methylated in MPM [44]. This Are small non-coding RNA molecules that regulate gene expression by binding to mRNA targets leading to their degradation or inhibiting their translation mTOR pathway mTOR (mammalian target of rapamycin) is a key protein which when activated leads to increased production of multiple proteins' [45,46]. The Wnt signaling pathway is deregulated by promoter methylation of its regulatory genes in MPM.…”
Section: In Favor Of Mpmmentioning
confidence: 99%